Existence of the eigenvalues of one differential operator dependent on parameter - Degutis, J.; Strelicas, Š. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Ш. И. Стрелиц, Ю. Э. Дегутис. Об одном методе доказательства существования собственных значений для одного дифференциального оператора с краевыми условиями, зависящими от параметра J. Degutis, S. Strelicas. Vieno diferencialinio operatoriaus, priklausančio nuo parametro, nuosavų reikšmių egzistavimas